Tactile force measurement of fingertips during manual operation to realize precision assembly by industrial robots. (December 2021) - Suzuki, Hikaru; Yamashita, Takahito; Tasaki, Ryosuke
Abstract: In this study, we aim to realize a precision assembly robot system that can perform all kinds of tasks without failure. Specifically, we focus on fitting precision parts, which is considered difficult with the current technology, and eliminate "assembly failure" such as biting of shafts and holes by referring to the feeling of human fingertips, and aim to reduce total assembly time. This will solve problems such as "high installation costs", "difficult to set for each product", and "assembly work that cannot be automated". This paper reports on the configuration and validity of the tactile force measurement system that measures tactile force information during assembly task. By proving the validity of this system, we prove that the tactile force data during actual work can be collected correctly. In addition, its correct data are compared to show that there is a difference in tactile force information on successful and unsuccessful fitting.